Cost-effectiveness of robotic hysterectomy versus abdominal hysterectomy in early endometrial cancer. Issue 11 (November 2020) - Lundin, Evelyn Serreyn; Carlsson, Per; Wodlin, Ninnie Borendal; Nilsson, Lena; Kjölhede, Preben
Abstract : Objectives: To compare total costs for hospital stay and post-operative recovery between robotic and abdominal hysterectomy in the treatment of early-stage endometrial cancer provided in an enhanced recovery after surgery (ERAS) setting. Costs were evaluated in relation to health impact, taking a societal perspective. Methods: Cost analysis was based on data from an open randomized controlled trial in an ERAS setting at a Swedish tertiary referral university hospital: 50 women with low-risk endometrial cancer scheduled for surgery between February 2012 and May 2016 were included; 25 women were allocated to robotic and 25 to abdominal hysterectomy. We compared the total time in the operating theater, procedure costs, post-operative care, length of hospital stay, readmissions, informal care, and sick leave as well as the health-related quality of life until 6 weeks after surgery. The comparison was made by using the EuroQoL group form with five dimensions and three levels (EQ-5D). The primary outcome measure was total cost; secondary outcomes were quality-adjusted life-years (QALYs) and cost per QALY. The costs were calculated in Swedish Krona (SEK). Results: Age (median (IQR) 68 (63–72) vs 67 (59–75) years), duration of hospital stay (ie, time to discharge criteria were met) (median (IQR) 36 (36–36) vs 36 (36–54) hours), and sick leave (median (IQR) 25 (17–30) vs 31 (36–54) days) did not differ between the robotic and abdominal group. Time of surgery was significantly longer in the robotic group than in the abdominal group (median (IQR) 70 (60–90) vs 56 (49–84) min; p<0.05). The robotic group recovered significantly faster as measured by the EQ-5D health index and gained 0.018 QALYs until 6 weeks after surgery. Total costs were 20% higher for the robotic procedure (SEK71 634 vs SEK59 319). The total cost per QALY gained for women in the robotic group was slightly under SEK700 000. Conclusions: Robotic hysterectomy used in an ERAS setting in the treatment of early endometrial cancer improved health within 6 weeks after the operation at a high cost for the health gained compared with abdominal hysterectomy. The productivity loss and informal care were lower for robotic hysterectomy, while healthcare had a higher procedure cost that could not be offset by the higher cost due to complications in the abdominal group.